Uji Kelayakan Panduan Praktikum Perkembangan Hewan Berbasis Project Based Learning Pada Materi Regenerasi - Novia Anggraini; Jodion Siburian; Winda Dwi Kartika (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The practicum guide used in animal development practicum is still simple and does not direct students to do practicum independently. This study aims to obtain the results of the development and feasibility of an animal development practicum guide based on project-based learning in regeneration material. This research is Research and development with a 4D development model with the stages of define, design, develop and disseminate. Data collection uses a material validation questionnaire, media and student responses. The test subjects were Biology Education students at the University of Jambi who were taking the Animal Development Practicum Course. The results of material validation obtained a score of 84.35% with very good criteria, the results of media validation obtained a score of 88% with very good criteria. It is stated that this practicum guide is feasible to be tested by students in the Animal Development Practicum Course.